Effect of Exercise on Blood Pressure in Type 2 Diabetes: A Randomized Controlled Trial - Dobrosielski, Devon A. (Springer-Verlag, 2012)
BACKGROUND: Increased blood pressure (BP) in type 2 diabetes (T2DM) markedly increases cardiovascular disease morbidity and mortality risk compared to having increased BP alone. OBJECTIVE: To investigate whether exercise reduces suboptimal levels of untreated suboptimal BP or treated hypertension. DESIGN: Prospective, randomized controlled trial for 6 months. SETTING: Single center in Baltimore, MD, USA. PATIENTS: 140 participants with T2DM not requiring insulin and untreated SBP of 120–159 or DBP of 85–99 mmHg, or, if being treated for hypertension, any SBP <159 mmHg or DBP < 99 mmHg; 114 completed the study. INTERVENTION: Supervised exercise, 3 times per week for 6 months compared with general advice about physical activity. MEASUREMENTS: Resting SBP and DBP (primary outcome); diabetes status, arterial stiffness assessed as carotid-femoral pulse-wave velocity (PWV), body composition and fitness (secondary outcomes). RESULTS: Overall baseline BP was 126.8 ± 13.5 / 71.7 ± 9.0 mmHg, with no group differences. At 6 months, BP was unchanged from baseline in either group, BP 125.8 ± 13.2 / 70.7 ± 8.8 mmHg in controls; and 126.0 ± 14.2 / 70.3 ± 9.0 mmHg in exercisers, despite attaining a training effects as evidenced by increased aerobic and strength fitness and lean mass and reduced fat mass (all p < 0.05), Overall baseline PWV was 959.9 ± 333.1 cm/s, with no group difference. At 6-months, PWV did not change and was not different between group; exercisers, 923.7 ± 319.8 cm/s, 905.5 ± 344.7, controls. LIMITATIONS: A completion rate of 81 %. CONCLUSIONS: Though exercisers improve fitness and body composition, there were no reductions in BP. The lack of change in arterial stiffness suggests a resistance to exercise-induced BP reduction in persons with T2DM.